Соглашение о международной дорожной перевозке опасных грузов (долог) - United Nations Economic Commission for Europe (United Nations, 2021)
The Agreement concerning the International Carriage of Dangerous Goods by Road (ADR) is intended to increase the safety of international transport of dangerous goods by road. Regularly amended and updated since its entry into force, it contains the conditions under which dangerous goods may be carried internationally. This revised version is based on amendments applicable as from 1 January 2021. It contains new or revised provisions concerning in particular the carriage of electric storage systems (including lithium batteries installed in cargo transport units and defective batteries), of medical waste and of radioactive material. Until now, the title of ADR was the